2012
DOI: 10.1080/02626667.2011.637041
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of flood frequency after forest fires in small ungauged basins based on uncertain measurements

Abstract: A methodology is proposed for constructing flood frequency curves before and after forest fires in small ungauged basins. It follows the rainfall-based derived distribution approach using Monte Carlo simulation and allowing for uncertainty in some of the variables involved. The generalized extreme value distribution for annual maximum rainfall is used, combined with the SCS-CN method for estimating rainfall excess, and the rational method for peak flow estimation. For pre-fire conditions, uncertainty in the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Additionally, Segura-Beltrán et al [13] analyzed the flash flood of the Girona River (Spain) in 2007 and found that some human-induced factors, such as artificially narrow stream width, walls, and roads, caused the overbank flow. Similar findings from other researches [12,36,[60][61][62][63] in watersheds very close to the study area (Chalkidiki region) showed the significant influence of…”
Section: Discusion On Flood Generation Causessupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, Segura-Beltrán et al [13] analyzed the flash flood of the Girona River (Spain) in 2007 and found that some human-induced factors, such as artificially narrow stream width, walls, and roads, caused the overbank flow. Similar findings from other researches [12,36,[60][61][62][63] in watersheds very close to the study area (Chalkidiki region) showed the significant influence of…”
Section: Discusion On Flood Generation Causessupporting
confidence: 90%
“…The lag time was defined by calculating the difference between the time of the precipitation peak and the time of the observed peak discharge at the outlet point of the watershed. To estimate the hydrographs of the two rainfalls (October 2006 and February 2010) in the Vatonias watershed, the SCS-CN model was used, a well-known and widely applied model in many countries [29][30][31][32][33] and in Greece [22,[34][35][36][37][38][39][40][41][42][43]. The CN is a dimensionless empirical parameter for predicting runoff and infiltration from rainfall excess [39].…”
Section: Hydrological Modelingmentioning
confidence: 99%
“…The accuracy of flood hazard assessments is limited by the fact that most drainage basins, including urban ones, are poorly gauged (Nalbantis 1995) or even ungauged and affected by changes such as forest fires (Nalbantis and Lymperopoulos 2012;Batelis and Nalbantis 2014). When advancing a step further, specifically to flood damage assessments, the data scarcity problem is accentuated and damage estimation methods inevitably become crude Merz et al 2010).…”
Section: Objectivementioning
confidence: 99%
“…In cases with erroneous DSMs or rainfall, we use quantiles with 90% probability of nonexceedance, that is, the 90% quantile of A , d i , V i , and W i , respectively denoted as A90, d90 i , V90 i , and W90 i for each cross‐section i . The selection of probability is dictated by two conflicting requirements (Candela, Aronica, & Santoro, ; Nalbantis & Lymperopoulos, ): the desire for a high degree of safety and an acceptable accuracy that is achievable using reasonable sample sizes in Monte Carlo simulations.…”
Section: Methodsmentioning
confidence: 99%